ANALISIS SPASIAL INFILTRASI AIR PADA LAHAN USAHA TANI HORTIKULTURA DI DAS MIKRO RURUKAN MINAHASA - Bobby J. Polii (EKOTON, 2014)
The results of previous studies have shown how patterns of land management, state of the slope, and the interactive influence of climate on hydrological properties and soil quality. The purpose of this study to identify the values and spatial distribution of infiltration parameters of water in horticultural farm land as a material management plan for the land in December of micro watershed Rurukan. Infiltration of water at ground level has been measured at the transect along the 22m with pressurized water Guelph Permeameter 2 or 5 or 10 cm. infiltration and soil permeability has been calculated based on the early time flow data (transient flow) and steady flow (steady state flow). The results showed that initial soil moisture content along the transect erosion plot higher than a month after planting there was a downward trend in the spatial moisture content from the top of the slope to the foot of the terraced plots. Moisture content differences at each measurement point are a local variety of symptoms caused by the ground processing activities and making the porch and terrace. But trends change soil density increased along the top of the slope to the foot of the slope. Initial permeability of the soil along the transect terrace relatifly lower than the permeability of a month later. Local diversity of faktors have caused the value of the permeability of the soil does not have a consistent pattern. The higher the volume of rainfall and the longer the duration of the rain so the soil eroded bigger. In the picture also appears that the treatment cycle terraces on eroding land larger than the cycle of land are treated deck. Concluded that there is spatial and temporal variability infiltration, moisture content, and density of land in the area of horticulture farming Rurukan micro-watersheds. However, further study needs to be done about the spatial patterns of water infiltration due to a variety of horticulture crops and soil management methods.